If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(a + 6) + -7a = 0 Reorder the terms: 5(6 + a) + -7a = 0 (6 * 5 + a * 5) + -7a = 0 (30 + 5a) + -7a = 0 Combine like terms: 5a + -7a = -2a 30 + -2a = 0 Solving 30 + -2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -2a = 0 + -30 Combine like terms: 30 + -30 = 0 0 + -2a = 0 + -30 -2a = 0 + -30 Combine like terms: 0 + -30 = -30 -2a = -30 Divide each side by '-2'. a = 15 Simplifying a = 15
| 16X+8=20X+25 | | -8x-4=-4x+16 | | 12x+16=5x+30 | | x+14=-2x+26 | | x^3-11x^2-20x=0 | | 5x+1=3x+8 | | x+-4=-8 | | -7x-16=-3x-12 | | 5x-11=-2x+31 | | 8x+13=11x-23 | | 24t-.8t^2=90 | | 6x-15=12x+20 | | 5r+3r=10 | | x^3+4x-2=0 | | 24t-8t^2=90 | | 9x+3x-10=3(3x+1) | | 8x^2+29x+15= | | 2/10= | | 4x^2-12x+45=0 | | 12x-17=6x+25 | | x^3+2x^2=520 | | Isy=2x-3 | | (x^2)-2x+1=0 | | 18+-(18)= | | -2x-3=-7 | | ln(x-2)+ln(x+2)=ln(2x+11) | | 4x^2-23x+39=2x+3factorize | | 27j-6=17j+7 | | 4x-2=9x-3 | | 2y+12=4y-4 | | 12+10=5a+7-8a | | 4t-6=6t+12 |